Why do the Global Warming Responses of Land‐Surface Models and Climatic Dryness Metrics Disagree?. Issue 8 (8th August 2022) - Scheff, Jacob; Coats, Sloan; Laguë, Marysa M.
Abstract: Earth System Models' complex land components simulate a patchwork of increases and decreases in surface water availability when driven by projected future climate changes. Yet, commonly‐used simple theories for surface water availability, such as the Aridity Index (P/E0) and Palmer Drought Severity Index (PDSI), obtain severe, globally dominant drying when driven by those same climate changes, leading to disagreement among published studies. In this work, we use a common modeling framework to show that Earth System Model (ESM) simulated runoff‐ratio and soil‐moisture responses become much more consistent with the P/E0 and PDSI responses when several previously known factors that the latter do not account for are cut out of the simulations. This reconciles the disagreement and makes the full ESM responses more understandable. For ESM runoff ratio, the most important factor causing the more positive global response compared to P/E0 is the concentration of precipitation in time with greenhouse warming. For ESM soil moisture, the most important factor causing the more positive global response compared to PDSI is the effect of increasing carbon dioxide on plant physiology, which also drives most of the spatial variation in the runoff ratio enhancement. The effect of increasing vapor‐pressure deficit on plant physiology is a key secondary factor for both. Future work will assess the utility of both the ESMs and the simple indices for understanding observed, historical trends. Plain Language Summary: Rivers and groundwater provide almost all water used by humans, and soil moisture is critical for vegetation and crops worldwide. Supercomputer model simulations of rivers, groundwater and soil moisture under future global warming routinely project that some world regions will experience increases in the availability of these resources, while others will experience decreases. Yet the simple formulas that scientists have traditionally relied on to measure climatic "drought" and "aridity" obtain large future decreases in water availability (drying) almost everywhere. This has led to confusion in prior studies and reports. In this study, we resolve this apparent paradox by pinpointing exactly why the supercomputer simulations are less pessimistic than the simple formulas. For rivers and groundwater, the most important reason is that precipitation gets "flashier" and more intense with global warming. For soil moisture, the most important reason is that increasing carbon dioxide allows vegetation to use less water, keeping more water in the soil. Both of these processes are included in the computer models, but not in the simple formulas. This new understanding gives us greater confidence that the computer models are behaving reasonably. Key Points: Community Land Model 5 runoff ratio and soil moisture responses to climate change closely follow the Aridity Index (P/E0 ) and Palmer Drought Severity Index (PDSI) in a simplified simulation Runoff ratio increases much more than P/E0 in full simulations primarily due to changes in the temporal pattern of precipitation Soil moisture increases more than PDSI in full simulations primarily due to CO2 and vapor pressure deficit effects on plant physiology